Obszary wykorzystania decyzyjnego rachunku kosztów w zarządzaniu procesami logistycznymi na przykładzie transportu - Piechota, Robert (The Areas of Using Decision Cost Accounting in Management of Transportation Processes, 2006)
The logistic processes of transportation need to bear considerable expenditures. It is more important to use decision cost accounting, which gives the possibility to make the rational decisions in a sphere of transportation activities of an enterprise. The elaboration shows the areas of using decision cost account in management of transportation processes. The purpose of elaboration is to underline the need to minimalize the cost of logistic systems as a very important factor of efficiency increase, during the management of an enterprise.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 51-57